Visible-light-enabled aerobic synthesis of benzoin bis-ethers from alkynes and alcohols. Issue 24 (20th November 2018) - Lei, Wen-Long; Yang, Biao; Zhang, Qing-Bao; Yuan, Pan-Feng; Wu, Li-Zhu; Liu, Qiang
Abstract : The first visible-light enabled metal-free aerobic protocol for one-pot synthesis of benzoin bis-ethers from alkenes and alcohols has been developed at room temperature. Abstract : A new, facile, atom-economical and good regioselective method for the synthesis of benzoin bis-ethers has been developed via directly using readily available alkynes and alcohols as raw materials under visible light irradiation. The protocol utilizes commercial Mes-Acr + ClO4 − as an organophotoredox catalyst and air (O2 ) as a green sustainable reagent. A range of benzoin bis-ether derivatives were easily and efficiently obtained in a one-pot procedure at room temperature, and water is the by-product.